Demographic, clinical and radiological characteristics of patients with acute ischemic stroke and acute symptomatic seizures - Baljak, Anja; Kovačević, Maša (Medicinski podmladak, 2025)
Introduction: A growing number of stroke survivors face various stroke complications, including acute symptomatic seizures. Symptomatic seizures are associated with longer hospitalizations, negative functional outcomes, and lower quality of life for patients after a stroke, and a better understanding of risk factors for their occurrence can facilitate their early identification and improve treatment.   The Aim: Identification of demographic, clinical, and radiological characteristics of patients with an acute ischemic stroke and acute symptomatic seizures, as well as identification of predictors of their occurrence in this patient population.   Material and Methods: A retrospective study of cases and controls was conducted, which included 21 patients treated for acute symptomatic seizures after an acute ischemic stroke in the  Department of Emergency Neurology, Clinic for Neurology, University Clinical Center of Serbia. The control group consisted of 149 randomly selected patients treated for ischemic stroke, but no acute symptomatic seizures treated during the same period. From an electronic database, data on risk factors for stroke, localization, severity, and treatment of stroke, as well as EEG findings, were collected.   Results: Acute symptomatic seizure following ischemic stroke was observed in 2.65% of subjects, 13 (61.9%) male and 8 (38.1%) female . Out of these, 16 (76.2%) patients had acute epileptic seizures, while 5 (23.8%) patients had an acute status epilepticus. The average age of patients at the time of a stroke with an acute symptomatic seizure was 68.9±15.3 years. A significant correlation of acute symptomatic seizures was established with the age of the subjects at the time of a stroke (τ= 0.3799, p= 0.0148) and with mRS at discharge (τ= 0.383, p
Keywords: acute ischemic stroke, acute symptomatic seizures, epileptic seizures, status epilepticus